Secondary battery and electric device
Patent Information
- Application Number
- CN202411214805.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-30
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-08-30
AI Technical Summary
It is difficult for existing secondary batteries to take into account high energy density while improving circulation performance. The small layer spacing of graphite materials leads to poor kinetic performance, and volume expansion during circulation seriously affects life.
A double-layer negative electrode film layer structure is adopted. The first area uses a first negative electrode active material with low graphitization and high isotropy, and the second area uses a second negative electrode active material with a high capacity. By adjusting the structure and composition of the material, the cycling performance and energy density of the battery are improved.
The cycling performance of the secondary battery is improved, while taking into account high energy density, reducing volume expansion during the lithium deintercalation process and extending the battery life.
Smart Images

Figure CN119852317A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a secondary battery and an electrical device. Background Art
[0002] In recent years, as the application scope of secondary batteries has become more and more extensive, secondary batteries are widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, as well as power tools, electric bicycles, electric motorcycles, electric vehicles, aerospace and other fields. As secondary batteries have made great progress, higher requirements have been put forward for their energy density and cycle performance. Summary of the invention
[0003] The present application is made in view of the above problems, and its purpose is to provide a secondary battery and an electric device. The secondary battery of the present application can improve the cycle performance while taking into account the energy density.
[0004] In order to achieve the above-mentioned purpose, the present application provides a secondary battery, including a negative electrode plate, the negative electrode plate including a negative electrode current collector and a negative electrode film layer located on at least one surface of the negative electrode current collector, the negative electrode film layer having a first surface away from the negative electrode current collector and a second surface arranged opposite to the first surface, the thickness of the negative electrode film layer is recorded as H, the area within the thickness range from the first surface of the negative electrode film layer to 0.3H is recorded as the first area of the negative electrode film layer, and the area within the thickness range from the second surface of the negative electrode film layer to 0.3H is recorded as the second area of the negative electrode film layer, the first area includes a first negative electrode active material, the second area includes a second negative electrode active material, the first negative electrode active material includes primary particles of a first artificial graphite, the powder OI value of the first negative electrode active material is 3-6, and the degree of graphitization is 91%-93.5%, and the gram capacity of the second negative electrode active material is greater than the gram capacity of the first negative electrode active material. By setting the negative electrode film layer as a double layer, the first region uses the above-mentioned first negative electrode active material, and the second region uses the above-mentioned second negative electrode active material, it is beneficial to improve the cycle performance of the secondary battery while taking into account the energy density.
[0005] In some embodiments, the powder OI value of the first negative electrode active material is 3-3.8, and / or the graphitization degree is 91.0%-92.5%, which is beneficial to improve the structural stability of the SEI film and the cycle life of the secondary battery.
[0006] In some embodiments, the first negative electrode active material has D / I G The value is 0.08-0.17; among them, I D It represents the D peak intensity at 1350±50cm-1 in the Raman spectrum of the material, IG Indicates the G peak intensity at 1580±50cm-1 in the Raman spectrum of the material; I D / I G The value represents the ratio of the D peak intensity to the G peak intensity. This is beneficial to reducing the defects of the first negative electrode active material of the negative electrode, reducing the active lithium consumption during the cycle and storage of the secondary battery, and thus improving the life performance of the secondary battery.
[0007] In some embodiments, the first negative electrode active material has D / I G The value is 0.1-0.15.
[0008] In some embodiments, the gram capacity of the second negative electrode active material is greater than 359 mAh / g, which is beneficial to increase the gram capacity of the negative electrode film layer and the energy density of the secondary battery.
[0009] In some embodiments, the gram capacity of the first negative electrode active material is 335 mAh / g-350 mAh / g, which is beneficial for improving the cycle performance of the secondary battery while taking into account the energy density.
[0010] In some embodiments, the gram capacity of the first negative electrode active material is 335 mAh / g-345 mAh / g; and / or the gram capacity of the second negative electrode active material is 360 mAh / g-366 mAh / g. This is beneficial to improving the cycle performance of the secondary battery while taking into account the energy density.
[0011] In some embodiments, the powder compaction density of the first negative electrode active material at 50000 N is less than the powder compaction density of the second negative electrode active material at 50000 N. This is beneficial to improving the kinetic performance and cycle performance of the secondary battery while taking into account the energy density of the secondary battery.
[0012] In some embodiments, the powder compaction density of the first negative electrode active material under 50000 N is 1.65 g / cc-1.83 g / cc; and / or the powder compaction density of the second negative electrode active material under 50000 N pressure is 1.95 g / cc-2.04 g / cc. This is conducive to reducing the volume expansion of the secondary battery during the cycle, thereby improving the life performance of the secondary battery, while taking into account the energy density of the secondary battery.
[0013] In some embodiments, the powder compaction density of the first negative electrode active material at 50000N is 1.65g / cc-1.71g / cc; and / or the powder compaction density of the second negative electrode active material at 50000N pressure is 1.96-2.02g / cc.
[0014] In some embodiments, the graphitization degree of the first negative electrode active material is less than the graphitization degree of the second negative electrode active material. Thus, the secondary battery can improve the cycle performance while taking into account the energy density.
[0015] In some embodiments, the graphitization degree of the second negative electrode active material is 94.0%-96.0%, which is beneficial to improve the energy density of the secondary battery.
[0016] In some embodiments, the second negative electrode active material has a graphitization degree of 94.2%-95.8%.
[0017] In some embodiments, the volume distribution particle size Dv50 of the first negative electrode active material is 9.0 μm-13.5 μm; and / or the volume distribution particle size Dv50 of the second negative electrode active material is 14.5 μm-18.0 μm.
[0018] In some embodiments, the volume distribution particle size Dv50 of the first negative electrode active material is 12.5-13.5 μm; and / or the volume distribution particle size Dv50 of the second negative electrode active material is 15.0 μm-17.5 μm.
[0019] In some embodiments, the specific surface area of the first negative electrode active material is less than or equal to the specific surface area of the second negative electrode active material.
[0020] In some embodiments, the specific surface area of the first negative electrode active material is 0.8 m 2 / g-1.8m 2 / g; and / or, the specific surface area of the second negative electrode active material is 0.8m 2 / g-2.1m 2 / g. This is beneficial to reduce the side reaction activity on the surface of the negative electrode active material and reduce the consumption of active ions by SEI film formation, thereby improving the cycle performance and first coulomb efficiency of the secondary battery.
[0021] In some embodiments, the gram capacity of the negative electrode plate is 348.0 mAh / g-355.0 mAh / g, which is beneficial for the secondary battery to take into account both energy density.
[0022] In some embodiments, the powder compaction density of the negative electrode film layer under a pressure of 50000 N is 1.60 g / cc-1.70 g / cc, which is beneficial to improving the kinetic performance and life performance of the negative electrode film layer while taking into account the energy density.
[0023] In some embodiments, the surface density of the negative electrode film layer is 10.0 mg / cm 2 -20.0mg / cm 2This is beneficial for the secondary battery to have both energy density and good storage performance and dynamic performance.
[0024] In some embodiments, the thickness of the negative electrode film layer is 70 μm-250 μm. This is beneficial for the secondary battery to have good storage performance and dynamic performance while taking into account energy density.
[0025] In some embodiments, in the negative electrode film layer, the mass ratio of the first negative electrode active material to the second negative electrode active material is 3:7-6:4. This is beneficial to improving the cycle performance of the secondary battery while taking into account the energy density.
[0026] In some embodiments, the second negative electrode active material includes a second artificial graphite, the La(110) of the second artificial graphite is 130nm-175nm, and the Lc(002) is 30nm-42nm, La(110) represents the crystallite size along the a-axis in the (110) crystal plane of the material, and Lc(002) may represent the crystallite size along the c-axis in the (002) crystal plane of the material. Thus, it is beneficial for the secondary battery to have a high energy density.
[0027] In some embodiments, La(110) of the second artificial graphite is 132nm-172nm, and Lc(002) is 30nm-36nm, which is beneficial for the secondary battery to have a high energy density.
[0028] In some embodiments, La(110) / Lc(002) is 3.5-5.5, which is beneficial for the secondary battery to have a high energy density.
[0029] In some embodiments, a charge and discharge test is performed on a button cell prepared from the second artificial graphite at a lithium removal rate of 0.1C and a lithium insertion rate of 0.05C, respectively, to obtain a charge and discharge curve in the range of 0.005V-2.0V, and in the discharge curve, there is a lithium insertion platform in the voltage range of 0.005V-0.070V, and the discharge capacity corresponding to the lithium insertion platform accounts for more than 43% of the total discharge capacity of the button cell. This is beneficial to improving the energy density of the secondary battery.
[0030] In some embodiments, the ratio X of the discharge capacity corresponding to the lithium embedded platform to the total discharge capacity of the button cell is 43%-47%.
[0031] In some embodiments, the second artificial graphite includes secondary particles, which is beneficial to reduce the volume expansion of the second artificial graphite, thereby improving the cycle life of the secondary battery.
[0032] In some embodiments, the particle size distribution (Dv90-Dv10) / Dv50 of the second negative electrode active material is 0.9-1.25, which is beneficial to improve the active ion and electron transport performance in the negative electrode film layer, thereby improving the kinetic performance of the secondary battery.
[0033] The second aspect of the present application provides an electric device, comprising the secondary battery of the first aspect of the present application. Since the electric device of the present application comprises the secondary battery provided by the present application, it has at least the same advantages as the secondary battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is a schematic diagram of an embodiment of the negative electrode plate of the present application.
[0035] Figure 2 It is a schematic diagram of a battery cell according to an embodiment of the present application.
[0036] Figure 3 yes Figure 2 An exploded view of a battery cell according to an embodiment of the present application is shown.
[0037] Figure 4 is a schematic diagram of a battery module according to an embodiment of the present application.
[0038] Figure 5 It is a schematic diagram of a battery pack according to one embodiment of the present application.
[0039] Figure 6 yes Figure 5 An exploded view of a battery pack according to an embodiment of the present application is shown.
[0040] Figure 7 FIG. 1 is a schematic diagram of an electric device using a secondary battery according to an embodiment of the present application as a power source.
[0041] Description of reference numerals:
[0042] 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 battery cell; 51 shell; 52 electrode assembly; 53 top cover assembly; 10 negative electrode plate; 101 negative electrode current collector; 102 negative electrode film layer; 102a first surface; 102b second surface; 1021 first area; 1022 second area; 1023 middle area. DETAILED DESCRIPTION
[0043] Below, the embodiments of the negative electrode plate, secondary battery and electrical device of the present application are specifically disclosed in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0044] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0045] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0046] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0047] If not specifically stated, the terms used in this application have the commonly known meanings generally understood by those skilled in the art.
[0048] If not otherwise specified, the values of the parameters mentioned in this application can be measured using various test methods commonly used in the art, for example, they can be measured according to the test methods given in this application.
[0049] If not otherwise specified, in the present application, the term "active ions" refers to ions that can be intercalated and extracted back and forth between the positive electrode and the negative electrode of a secondary battery, including but not limited to lithium ions.
[0050] At present, in order to improve the energy density of secondary batteries, graphite materials with high gram capacity and high compaction density, such as natural graphite, are usually used. However, the interlayer spacing of high gram capacity graphite is small, which affects the dynamic performance of the battery, and the graphite structure is unstable due to volume expansion during the cycle, which seriously affects the cycle performance of the secondary battery. In addition, in order to improve the cycle performance of secondary batteries, graphite materials with low graphitization degree and large interlayer spacing are usually used, but low graphitization degree will cause the gram capacity and compaction density of graphite materials to deteriorate, affecting the energy density of the battery. Therefore, it is currently difficult to take into account energy density while improving cycle performance.
[0051] Based on this, the present application proposes a secondary battery and an electrical device, thereby enabling the secondary battery to improve cycle performance while taking into account energy density.
[0052] The present application provides a secondary battery. The term "secondary battery" mentioned herein refers to a battery cell, a battery module or a battery pack. Each of the above is described below.
[0053] A secondary battery cell includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is set between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.
[0054] Negative electrode
[0055] The secondary battery of the present application includes a negative electrode plate, which includes a negative electrode current collector and a negative electrode film layer located on at least one surface of the negative electrode current collector, wherein the negative electrode film layer has a first surface away from the negative electrode current collector and a second surface arranged opposite to the first surface, the thickness of the negative electrode film layer is recorded as H, the area within the thickness range from the first surface of the negative electrode film layer to 0.3H is recorded as the first area of the negative electrode film layer, and the area within the thickness range from the second surface of the negative electrode film layer to 0.3H is recorded as the second area of the negative electrode film layer, the first area includes a first negative electrode active material, the second area includes a second negative electrode active material, the first negative electrode active material includes primary particles of a first artificial graphite, the powder OI value of the first negative electrode active material is 3-6, and the degree of graphitization is 91%-93.5%, and the gram capacity of the second negative electrode active material is greater than the gram capacity of the first negative electrode active material.
[0056] See also Figure 1 , which shows a schematic diagram of an embodiment of the negative electrode sheet of the present application. Figure 1 As shown, the negative electrode sheet 10 includes a negative electrode current collector 101 and a negative electrode film layer 102 formed on at least one surface of the negative electrode current collector 101. The negative electrode film layer 102 has a first surface 102a away from the negative electrode current collector 101 and a second surface 102b arranged opposite to the first surface 102a. The thickness of the negative electrode film layer 102 is recorded as H. The thickness H of the negative electrode film layer refers to the thickness of the negative electrode film layer located on one side of the negative electrode current collector. The area within the range of 0.3H thickness from the first surface 102a of the negative electrode film layer is recorded as the first area 1021 (upper layer) of the negative electrode film layer. The area within the range of 0.3H thickness from the second surface 102b of the negative electrode film layer is recorded as the second area 1022 (lower layer) of the negative electrode film layer. The first area 1021 includes a first negative electrode active material, and the second area 1022 includes a second negative electrode active material. The area between the first area 1021 and the second area 1022 is recorded as the middle area 1023. It is easy to understand that within the scope of the middle region 1023, there may be only the first negative electrode active material, only the second negative electrode active material, both the first negative electrode active material and the second negative electrode active material, or other negative electrode active materials known in the art in addition to the first negative electrode active material and the second negative electrode active material of the present application.
[0057] It should be understood that Figure 1 In the embodiment shown in FIG. 1 , the second surface 102 b contacts the upper surface of the negative electrode current collector 101 , but the structure of the negative electrode sheet of the present application is not limited thereto. For example, there may be an additional layer between the negative electrode film layer 102 and the negative electrode current collector 101 . In this case, the second surface 102 b does not directly contact the negative electrode current collector 101 .
[0058] It should also be understood that Figure 1 Although the graphic shows clear boundaries between areas, there may not be such clear interfaces in the product.
[0059] In the present application, by setting the negative electrode film layer as a double layer, the negative electrode plate can still maintain a good pore structure, low tortuosity, a short ion transmission path and a high ion conduction efficiency at a higher compaction density. In addition, by using low graphitization and highly isotropic graphite on the side away from the current collector (ie, the first region 1021), the volume expansion during lithium insertion and extraction can be effectively reduced, thereby improving the cycle performance. By using a second negative electrode active material with a higher gram capacity on the side close to the current collector (ie, the second region 1022), the energy density of the battery can be taken into account.
[0060] In the present application, the first negative electrode active material included in the first region includes primary particles of the first artificial graphite, the powder OI value of the first negative electrode active material is 3-6, and the degree of graphitization is 91%-93.5%. The inventors have found that by using the above-mentioned first negative electrode active material in the first region, it has a lower degree of graphitization, so that the graphite material has a larger interlayer spacing, so the volume expansion during lithium insertion and extraction is smaller, which is beneficial to improve the structural stability of the SEI film and improve the cycle life; at the same time, the graphite material has a higher degree of isotropy, which can effectively alleviate the volume expansion caused by lithium insertion and extraction, further improve the stability of the SEI film, and improve the cycle life. In addition, the primary particles are beneficial to reduce the surface defects of graphite and reduce the consumption of active ions during the cycle of the secondary battery, thereby improving the cycle life of the secondary battery.
[0061] Exemplarily, the powder OI value of the first negative electrode active material may be 3, 4, 5, 6, or a value between the ranges consisting of any two of them. Exemplarily, the degree of graphitization of the first negative electrode active material may be 91%, 91.5%, 92.0%, 92.5%, 93.0%, 93.5%, or a value between the ranges consisting of any two of them. In some optional embodiments, the powder OI value of the first negative electrode active material is 3-3.8, and / or the degree of graphitization is 91.0%-92.5%.
[0062] In the present application, the gram capacity of the second negative electrode active material is greater than the gram capacity of the first negative electrode active material. In the present application, the second negative electrode active material located in the second region has a higher gram capacity, which is beneficial to increase the gram capacity of the negative electrode film layer, so that the secondary battery can take into account the energy density; the first negative electrode active material located in the first region can improve the cycle performance.
[0063] In some embodiments, the first negative electrode active material has D / I G The value is 0.08-0.17; among them, I D Indicates that the Raman spectrum of the material is at 1350±50cm -1 The D peak intensity at I G Indicates that the Raman spectrum of the material is 1580±50cm -1 The G peak intensity at I D / I G The value represents the ratio of the D peak intensity to the G peak intensity. D / I G The value is within the above range, which is beneficial to reduce the defects of the first negative electrode active material, reduce the active lithium consumption during the cycle and storage process, and thus improve the life performance. D / IG The value may be 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17 or a range consisting of any two arrays thereof. In some optional embodiments, the I of the first negative electrode active material D / I G The value is 0.1-0.15.
[0064] In some embodiments, the gram capacity of the first negative electrode active material is 335mAh / g-350mAh / g. By making the gram capacity of the first negative electrode active material within the above range, it is beneficial for the secondary battery to have good cycle performance while taking into account energy density. Exemplarily, the gram capacity of the first negative electrode active material can be 335mAh / g, 340mAh / g, 345mAh / g, 350mAh / g or a value between the ranges consisting of any two of them. In some optional embodiments, the gram capacity of the first negative electrode active material can be 335mAh / g-345mAh / g.
[0065] In some embodiments, the gram capacity of the second negative electrode active material is 359.0mAh / g or more. By making the negative electrode active material in the second region have a high gram capacity, it is beneficial to improve the energy density of the secondary battery. Exemplarily, the gram capacity of the second negative electrode active material is 359mAh / g, 360mAh / g, 361mAh / g, 362mAh / g, 363mAh / g, 364mAh / g, 365mAh / g, 366mAh / g, 367mAh / g, 368mAh / g, 369mAh / g, 370mAh / g or a value between the ranges consisting of any two of them. In some optional embodiments, the gram capacity of the second negative electrode active material is 360mAh / g-366mAh / g. By making the gram capacity of the second negative electrode active material in the above range, it is beneficial to improve the energy density of the secondary battery.
[0066] In some embodiments, the powder compaction density of the first negative electrode active material at 50000 N is less than the powder compaction density of the second negative electrode active material at 50000 N. In the present application, the second negative electrode active material located in the second region has a higher powder compaction density, which is beneficial to improving the energy density of the secondary battery, and the first negative electrode active material located in the first region has a smaller powder compaction density, which is beneficial to reducing the tortuosity of the negative electrode film layer and reducing the active ion migration path, thereby improving the kinetic performance and cycle performance of the secondary battery.
[0067] In some embodiments, the powder compaction density of the first negative electrode active material at 50000N is 1.65g / cc-1.83g / cc; and / or, the powder compaction density of the second negative electrode active material at 50000N pressure is 1.95g / cc-2.04g / cc. By making the powder compaction density of the first negative electrode active material within the above range, it is beneficial to reduce the volume expansion during the cycle of the secondary battery, thereby improving the life performance of the secondary battery; in addition, making the powder compaction density of the second negative electrode active material within the above range is beneficial to improve the energy density of the secondary battery. Exemplarily, the powder compaction density of the first negative electrode active material at 50000N can be 1.65g / cc, 1.68g / cc, 1.70g / cc, 1.72g / cc, 1.75g / cc, 1.78g / cc, 1.80g / cc, 1.83g / cc or a value between the ranges consisting of any two of them. In some optional embodiments, the powder compaction density of the first negative electrode active material at 50000N is 1.65g / cc-1.71g / cc. Exemplarily, the powder compaction density of the second negative electrode active material at a pressure of 50000N can be 1.95g / cc, 1.96g / cc, 1.97g / cc, 1.98g / cc, 1.99g / cc, 2.00g / cc, 2.01g / cc, 2.02g / cc, 2.03g / cc, 2.04g / cc or a value between any two of them. In some optional embodiments, the powder compaction density of the second negative electrode active material at a pressure of 50000N is 1.96-2.02g / cc.
[0068] In some embodiments, the graphitization degree of the first negative electrode active material is less than that of the second negative electrode active material. In the present application, the first negative electrode active material located in the first region has a lower graphitization degree, and therefore, the interlayer spacing of the first negative electrode active material is larger, which is beneficial to reducing the volume expansion during the cycle of the secondary battery and improving the cycle performance of the secondary battery; in addition, the second negative electrode active material located in the second region has a higher graphitization degree, which is beneficial to increasing the gram capacity of the negative electrode film layer, thereby increasing the energy density of the secondary battery. As a result, the secondary battery can take into account both excellent cycle performance and high energy density.
[0069] In some embodiments, the degree of graphitization of the second negative electrode active material is 94.0%-96.0%. By making the degree of graphitization of the second negative electrode active material in the above range, it is beneficial for the second negative electrode active material to have a high compaction density and gram capacity, thereby improving the energy density of the secondary battery. Exemplarily, the degree of graphitization of the second negative electrode active material can be 94.0%, 94.5%, 95.0%, 95.5%, 96.0% or a value between the ranges consisting of any two of them. In some optional embodiments, the degree of graphitization of the second negative electrode active material is 94.2%-95.8%.
[0070] In some embodiments, the volume distribution particle size Dv50 of the first negative electrode active material is 9.0μm-13.5μm; and / or, the volume distribution particle size Dv50 of the second negative electrode active material is 14.5μm-18.0μm. By making the volume distribution particle size Dv50 of the first negative electrode active material and / or the second negative electrode active material within the above range, it is beneficial to improve the cycle performance and kinetic performance of the secondary battery while taking into account the energy density. Exemplarily, the volume distribution particle size Dv50 of the first negative electrode active material can be 9.0μm, 9.5μm, 10.0μm, 10.5μm, 11.0μm, 11.5μm, 12.0μm, 12.5μm, 13.0μm, 13.5μm or a value between the ranges consisting of any two of them. In some optional embodiments, the volume distribution particle size Dv50 of the first negative electrode active material is 12.5μm-13.5μm. In addition, illustratively, the volume distribution particle size Dv50 of the second negative electrode active material can be 14.5 μm, 15.0 μm, 15.5 μm, 16.0 μm, 16.5 μm, 17.0 μm, 17.5 μm, 18.0 μm, or a value between the ranges consisting of any two of them. In some optional embodiments, the volume distribution particle size Dv50 of the second negative electrode active material is 15.0 μm-17.5 μm.
[0071] In some embodiments, the specific surface area of the first negative electrode active material is less than or equal to the specific surface area of the second negative electrode active material.
[0072] In some embodiments, the specific surface area of the first negative electrode active material is 0.8-1.8 m 2 / g; and / or, the specific surface area of the second negative electrode active material is 0.8m 2 / g-2.1m 2 / g. By making the specific surface area of the first negative electrode active material within the above range, it is helpful to reduce the side reaction activity of the surface of the negative electrode active material, thereby reducing the consumption of active ions by SEI film formation, thereby improving the cycle performance of the secondary battery. In addition, by making the specific surface area of the second negative electrode active material within the above range, it is helpful to reduce the side reaction activity of the surface of the negative electrode active material, thereby reducing the consumption of active ions by SEI film formation, and improving the first coulombic efficiency and cycle performance of the secondary battery; on the other hand, it can also have higher active ion transport performance, thereby improving the kinetic performance of the secondary battery. Exemplarily, the specific surface area of the first negative electrode active material can be 0.8m 2 / g, 1.0m 2 / g, 1.2m 2 / g, 1.4m 2 / g, 1.6m 2 / g, 1.8m 2 / g or a value between any two of the ranges. For example, the specific surface area of the second negative electrode active material may be 0.8 m 2 / g, 1.0m 2 / g, 1.2m 2 / g, 1.4m 2 / g, 1.6m 2 / g, 1.8m 2 / g, 2.0m 2 / g, 2.1m 2 / g or a value between the ranges consisting of any two of them.
[0073] In some embodiments, the gram capacity of the negative electrode plate is 348.0mAh / g-355.0mAh / g. By making the gram capacity of the negative electrode plate in the above range, it is beneficial to improve the energy density of the secondary battery. Exemplarily, the gram capacity of the negative electrode plate can be 348.0mAh / g, 350.0mAh / g, 352.0mAh / g, 355.0mAh / g or a value between the ranges consisting of any two of them.
[0074] In some embodiments, the powder compaction density of the negative electrode film layer under a pressure of 50000N is 1.60g / cc-1.70g / cc. By making the powder compaction density of the negative electrode film layer within the above range, it is beneficial to maintain a good pore structure, reduce the tortuosity of the negative electrode film layer, shorten the active ion transmission path, thereby improving the kinetic performance and life performance of the negative electrode film layer, while taking into account high energy density. Exemplarily, the powder compaction density of the negative electrode film layer under a pressure of 50000N can be 1.60g / cc, 1.62g / cc, 1.64g / cc, 1.66g / cc, 1.68g / cc, 1.70g / cc or a value between the ranges consisting of any two of them. In some optional embodiments, the powder compaction density of the negative electrode film layer under a pressure of 50000N is 1.62g / cm 3 -1.68g / cm 3 .
[0075] In some embodiments, the surface density of the negative electrode film layer is 10.0 mg / cm 2 -20.0mg / cm 2 By making the surface density of the negative electrode film layer within the above range, it is beneficial for the negative electrode film layer to have high capacity, high active ion and electron transport performance, and thus it is beneficial for the secondary battery to have high energy density and good storage performance and kinetic performance. For example, the surface density of the negative electrode film layer can be 10 mg / cm 2 、12.0mg / cm 2 、15mg / cm 2 、18.0mg / cm 2 , 20mg / cm 2 Or a value between any two of the ranges formed by the values thereof. In some optional embodiments, the surface density of the negative electrode film layer is 12.0 mg / cm 2 -18.5mg / cm 2 .
[0076] In some embodiments, the thickness of the negative electrode film layer is 70μm-250μm. By making the thickness of the negative electrode film layer within the above range, it is beneficial for the negative electrode film layer to take into account high capacity, high active ion and electron transport performance, which is beneficial for the secondary battery to take into account high energy density and good storage performance and kinetic performance. Exemplarily, the thickness of the negative electrode film layer can be 70μm, 80μm, 90μm, 95μm, 100μm, 110μm, 120μm, 130μm, 140μm, 150μm, 160μm, 180μm, 200μm, 210μm, 220μm, 240μm, 250μm or a value between the ranges consisting of any two of them. In some optional embodiments, the thickness of the negative electrode film layer is 90μm-220μm.
[0077] In some embodiments, in the negative electrode film layer, the mass ratio of the first negative electrode active material to the second negative electrode active material is 3:7-6:4. By making the mass ratio of the first negative electrode active material to the second negative electrode active material within the above range, it is beneficial for the secondary battery to have excellent cycle performance while taking into account energy density. Exemplarily, the mass ratio of the first negative electrode active material to the second negative electrode active material can be 3:7, 4:6, 5:5, 6:4 or a ratio between the ranges consisting of any two of them.
[0078] In some embodiments, the second negative electrode active material includes a second artificial graphite, the La (110) of the second artificial graphite is 130nm-175nm, and the Lc (002) is 30nm-42nm, La (110) represents the crystallite size along the a-axis in the (110) crystal plane of the material, and Lc (002) can represent the crystallite size along the c-axis in the (002) crystal plane of the material. The increase in La of the second artificial graphite indicates that the crystallite size of the second artificial graphite increases, and the number of lithium-inserted sites on the surface of the second artificial graphite increases, so the gram capacity increases. In addition, the increase in crystallite size can also reduce the number of crystal boundaries of the second artificial graphite crystallites, so that the number of lithium-inserted sites increases, thereby reducing the adverse effects of gram capacity and powder compaction density, and thus improving the gram capacity and powder compaction density of the second artificial graphite. The Lc of the second artificial graphite is within the above range, which is conducive to reducing the stacking of graphite crystallites, thereby reducing the number of crystal boundaries between crystallites, and is conducive to increasing the number of lithium-inserted sites on the surface of the second artificial graphite, thereby increasing the gram capacity of the second artificial graphite. Thus, the second negative electrode active material located in the second region has a high gram capacity and a high compaction density, which is beneficial for the secondary battery to have a high energy density.
[0079] In some embodiments, the La(110) of the second artificial graphite is 132nm-172nm, and the Lc(002) is 30nm-36nm. By making the La(110) and Lc(002) of the second artificial graphite within the above range, it is beneficial to increase the gram capacity and compaction density of the second negative electrode active material, thereby facilitating the secondary battery to have a high energy density.
[0080] In some embodiments, La(110) / Lc(002) is 3.5-5.5. By making La(110) / Lc(002) within the above range, the grains in the graphite material are well developed and the number of crystallites is small, so there are fewer interfaces between the grains, which is beneficial to increase the lithium embedding sites on the surface of the artificial graphite, thereby helping to increase the gram capacity of the negative electrode active material. As a result, it is beneficial to increase the gram capacity of the negative electrode film layer, thereby improving the energy density of the secondary battery. Exemplarily, La(110) / Lc(002) can be 3.5, 3.8, 4.0, 4.2, 4.4, 4.6, 4.8, 5.0, 5.2, 5.5 or a value between the ranges consisting of any two of them. In some optional embodiments, the La(110) / Lc(002) of the second artificial graphite is 4.5-5.5.
[0081] In some embodiments, charge and discharge tests are performed on a button cell prepared from the second artificial graphite at a lithium desorption rate of 0.1C and a lithium insertion rate of 0.05C, respectively, to obtain a charge and discharge curve in the range of 0.005V-2.0V. In the discharge curve, there is a lithium insertion platform in the voltage range of 0.005V-0.070V, and the discharge capacity corresponding to the lithium insertion platform accounts for a proportion X of more than 43% of the total discharge capacity of the button cell.
[0082] In this application, the charge and discharge test is carried out by the following method: the sample powder is mixed with the conductive agent carbon black (SuperP), the binder polyvinylidene fluoride (PVDF) and the solvent N-methylpyrrolidone (NMP) in a mass ratio of 91.6:1.8:6.6 to make a slurry; the prepared slurry is coated on the surface of the negative electrode current collector copper foil, and dried in an oven for use; ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then LiPF6 is dissolved in the above organic solvent. The invention discloses a method for preparing an electrolyte with a concentration of 1 mol / L in a solvent; then, a metal lithium sheet is used as a counter electrode, a polyethylene (PE) film is used as an isolation membrane, and the electrolyte is assembled into a CR2430 button cell in an argon-protected glove box; after the button cell is allowed to stand for 12 hours, it is discharged at a constant current of 0.05C to 0.005V at 25°C, allowed to stand for 10 minutes, and then discharged at a constant current of 50μA to 0.005V, allowed to stand for 10 minutes, and then discharged at a constant current of 10μA to 0.005V; then, it is charged at a constant current of 0.1C to 2.0V, and the charge and discharge curve of the material is recorded.
[0083] In the present application, a button cell prepared with a second negative electrode active material is subjected to the above-mentioned charge and discharge test to obtain a charge and discharge curve. In the discharge curve, the discharge capacity corresponding to the lithium insertion platform in the voltage range of 0.005V to 0.070V accounts for more than 43% of the total discharge capacity of the button cell. The second negative electrode active material has a high gram capacity, which is beneficial to improving the energy density of the secondary battery. Although the mechanism is not yet clear, the inventors believe that during the lithium insertion process of the graphite material, as the amount of lithium ion insertion increases, graphite intercalation compounds of different orders, such as LiC24, LiC12, LiC6, etc., will gradually form. The formation of graphite intercalation compounds of different orders corresponds to lithium insertion platforms in different voltage ranges in the charge and discharge curve of the graphite material. Since the theoretical capacity of graphite intercalation compounds of different orders is different, for example, the theoretical capacity of LiC6 is 372mAh / g, while the theoretical specific capacity of LiC12 is 186mAh / g. Therefore, in the lithium insertion process, the more LiC6 (i.e., the lithium insertion platform corresponding to the voltage range of 0.005V-0.07V) is formed, the more the corresponding capacity contribution is, and the higher the gram capacity of the graphite material is. Exemplarily, the ratio X can be 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50% or a value between the ranges consisting of any two of them. In some embodiments, the ratio X of the discharge capacity corresponding to the lithium insertion platform to the total discharge capacity of the button battery is 43%-50%, optionally 43%-47%.
[0084] In some embodiments, the second artificial graphite includes secondary particles, which is conducive to reducing the orientation degree of the second artificial graphite, improving the isotropy of the second artificial graphite, reducing the volume expansion of the second artificial graphite, helping to reduce the damage of the SEI film caused by the volume expansion, and reducing the active ions consumed in forming a new SEI film, thereby improving the cycle life of the secondary battery.
[0085] In some embodiments, the particle size distribution (Dv90-Dv10) / Dv50 of the second negative electrode active material is 0.9-1.25. As a result, it is beneficial to improve the compaction density of the negative electrode film layer and the energy density of the secondary battery; in addition, it is also beneficial to form a reasonable pore structure between the particles of the negative electrode film layer, improve the active ion and electron transport performance in the negative electrode film layer, and thus improve the kinetic performance of the secondary battery. Exemplarily, the particle size distribution (Dv90-Dv10) / Dv50 of the second negative electrode active material is 0.90, 0.95, 1.00, 1.05, 1.10, 1.15, 1.20, 1.25 or a value between the ranges consisting of any two of them. In some optional embodiments, the particle size distribution (Dv90-Dv10) / Dv50 of the second negative electrode active material is 0.90-1.20.
[0086] In the present application, La (110) and Lc (002) of the material (second artificial graphite, etc.) can be measured using instruments and methods known in the art. For example, the negative electrode plate removed from the secondary battery can be cleaned with an organic solvent such as DMC and then dried. The cleaned negative electrode plate is then immersed in NMP for ultrasonic treatment to separate the copper foil to obtain the negative electrode material. After the negative electrode material is dried, it is sintered at 350°C-500°C, then washed with water for multiple times, and dried at 80°C to obtain the negative electrode active material. An X-ray diffractometer (such as Bruker D8 Discover) is used for testing. The test can refer to JIS K 0131-1996 and JB / T4220-2011 to obtain the peak intensity and half-maximum full width (FWHM) of the diffraction peak corresponding to the (110) crystal plane of the material, and the peak intensity and half-maximum full width (FWHM) of the diffraction peak corresponding to the (002) crystal plane of the material, and then calculated according to the Scherrer formula.
[0087] In the present application, the I of the material (first negative electrode active material, second negative electrode active material, etc.) D / I G Raman spectrometer can be used for testing. D The Raman spectrum of the material is 1350±50cm -1 The D peak intensity at I G The Raman spectrum of the material is 1580±50cm -1 The test conditions are: excitation wavelength of 532nm, grating of 600 lines, objective lens of 50 times, integration time of 10s, accumulation times of 3 times, surface scanning, obtain the D peak and G peak intensity of 100 points, calculate the I of 100 points D / I G , remove the largest and smallest 30 I D / I G The average value of the remaining 40 points is the I D / I G The testing instrument may be a Horiba LabRAM HR800 Raman spectrometer.
[0088] In the present application, the OI value of the powder of a material (the first negative electrode active material, the second negative electrode active material, etc.) refers to the graphite orientation of the material, which describes the consistency of the orientation of the crystals in the graphite material particles. The powder OI value of the material is the ratio of the peak area of the face (004) to the peak area of the face (110) obtained by testing the material using the X-ray diffraction method XRD. In the present application, the powder OI value of the material can be determined using instruments and methods known in the art. For example, an X-ray diffractometer (such as Bruker D8 Discover) can be used for testing. The test can refer to JIS K 0131-1996, JB / T 4220-2011 to obtain the X-ray diffraction spectrum of the powder sample. According to OI value = I 004 / I 110 The powder OI value of the sample is calculated. 004 is the integrated area of the diffraction peak of the 004 crystal plane of crystalline carbon in the powder sample, I 110 is the integrated area of the diffraction peak of the 110 crystal plane of crystalline carbon in the powder sample. In the X-ray diffraction analysis test of the present application, a copper target can be used as an anode target, and CuKα rays can be used as a radiation source with a wavelength of The scanning 2θ angle range was 20°-80°, and the scanning rate was 4° / min.
[0089] In the present application, the powder compaction density of the material (first negative electrode active material, second negative electrode active material, etc.) is the mass per unit volume of the powder under specified conditions, which can be measured by instruments and methods known in the art. For example, it can be measured by an electronic pressure testing machine (for example, a UTM7305 electronic pressure testing machine) with reference to GB / T 24533-2009. The exemplary test method is as follows: weigh 1g of sample powder and add a bottom area of 1.327cm 2 In the mold, the pressure is increased to 50000N, the pressure is maintained for 30s, and then the pressure is released and maintained for 10s. Then the powder compaction density of the material under the pressure of 50000N is recorded and calculated.
[0090] In the present application, the volume distribution particle sizes Dv10, Dv50, and Dv90 of the materials (e.g., the first negative electrode active material, the second negative electrode active material, etc.) respectively represent the particle sizes corresponding to the cumulative volume distribution percentages of the materials reaching 10%, 50%, and 90%, which can be measured using instruments and methods known in the art. For example, it can be measured using a laser particle size analyzer with reference to GB / T 19077-2016. The test instrument can be a Mastersizer 3000 laser particle size analyzer from Malvern Instruments Ltd., UK.
[0091] In the present application, the gram capacity of a material (first negative electrode active material, second negative electrode active material, etc.) is the ratio of the capacity that can be released by the active material to the mass of the active material, and can be tested by methods known in the art. An exemplary test method is as follows: the sample powder is mixed evenly with a conductive agent, a binder and optionally other additives in a certain mass ratio with a solvent to form a slurry; the prepared slurry is applied on the surface of the negative electrode current collector copper foil, dried in an oven and then used; the lithium salt is dissolved in an organic solvent to prepare an electrolyte; then a metal lithium sheet is used as a counter electrode, a polyethylene (PE) film is used as a separator, and the above electrolyte is assembled into a CR2430 button battery in an argon-protected glove box. After the button cell was left to stand for 12 hours, it was discharged at 0.15 mA constant current to 0.005 V at 25 ° C, left to stand for 10 minutes, and then discharged at 50 μA constant current to 0.005 V, left to stand for 10 minutes, and then discharged at 10 μA constant current to 0.005 V; then it was charged at 0.3 mA constant current to 2.0 V, and the first cycle charging capacity of the button cell was recorded. The ratio of the charging capacity to the sample mass is the gram capacity of the corresponding material (first negative electrode active material, second negative electrode active material, etc.).
[0092] In the present application, the graphitization degree of the material (the first negative electrode active material, the second negative electrode active material, etc.) is the proportion of carbon in the material in the form of a graphite structure, which can be tested using instruments and methods known in the art. For example, an X-ray diffractometer (such as Bruker D8 Discover) can be used for testing. The test can refer to JIS K 0131-1996 and JB / T 4220-2011 to obtain the average interlayer spacing d of the C(002) crystal plane in the material crystal structure. 002 Then according to the formula g = (0.344-d 002 ) / (0.344-0.3354)×100% to calculate the graphitization degree. In the above formula, d 002 It is the average interlayer spacing of the C(002) crystal plane in the material's crystal structure expressed in nanometers (nm).
[0093] In this application, the thickness of the negative electrode film layer has a well-known meaning in the art and can be tested by methods known in the art, such as using a micrometer (such as Mitutoyo 293-100, with an accuracy of 0.1 μm). The thickness range given in this application is the thickness range of the negative electrode film layer on one side of the negative electrode current collector.
[0094] In the present application, the specific surface area of a material (e.g., a first negative electrode active material, a second negative electrode active material, etc.) is the total area per unit mass of the material, which can be measured using instruments and methods known in the art. For example, it can be measured by nitrogen adsorption specific surface area analysis test method according to GB / T 19587-2017, and calculated using the BET (Brunauer Emmett Teller) method. The test instrument can be the Tri-Star 3020 specific surface area pore size analysis tester from Micromeritics, USA.
[0095] In the present application, primary particles and secondary particles have the meanings known in the art. Primary particles refer to non-agglomerated particles. Secondary particles refer to agglomerated particles formed by the aggregation of two or more primary particles. Primary particles and secondary particles can be distinguished by using a scanning electron microscope (SEM) image.
[0096] Method for preparing negative electrode sheet
[0097] The negative electrode sheet in the present application can be prepared in the following manner: provide a first slurry containing a first negative electrode active material and a second slurry containing a second negative electrode active material; apply the first slurry on the negative electrode collector, apply the second slurry on the first slurry, and obtain the negative electrode sheet after drying and cold pressing.
[0098] The preparation method of the first negative electrode active material in the present application comprises the following steps:
[0099] Pretreatment step: crushing and shaping the petroleum coke to obtain a shaped material with a volume distribution particle size Dv50 of 10 μm-14 μm; and
[0100] Graphitization step: subjecting the above-mentioned shaped material to a first graphitization treatment at 2400° C.-2800° C. to obtain a first negative electrode active material.
[0101] The present application uses petroleum coke as a raw material, and petroleum coke has high isotropy, so the prepared first negative electrode active material also has high isotropy, which is beneficial to reduce the volume expansion of the first negative electrode active material during lithium insertion and extraction, and improve the cycle life of the secondary battery. Exemplarily, the petroleum coke can be petroleum needle coke.
[0102] In the present application, the temperature of the first graphitization treatment is 2400°C-2800°C. By making the graphitization temperature within the above range, the grain growth and development of the graphite material can be controlled, so that the prepared graphite material has a larger interlayer spacing, which can reduce the volume expansion of the first negative electrode active material during the secondary battery cycle, maintain structural stability, and thus improve the life performance of the secondary battery. Exemplarily, the temperature of the first graphitization treatment can be 2400°C, 2500°C, 2600°C, 2700°C, 2800°C, or a value between the ranges consisting of any two of them.
[0103] In the present application, the graphitization treatment time is 2h-48h. For example, when the graphitization temperature is 2600°C, the graphitization time can be 2h, 4h, 8h, 20h, 48h or a value in the range formed by any two of these values.
[0104] In some embodiments, the sulfur content in the petroleum coke is less than or equal to 0.6%, and the volatile component content is less than or equal to 15%. Here, the so-called volatile component refers to volatile organic matter, such as alkanes, aromatic hydrocarbons, lipids, etc. The content of sulfur and volatile components in the first raw material is within the above range. During the graphitization process, the defects caused by the overflow of sulfur are reduced, which is conducive to reducing the defects of the first negative electrode active material, improving the stability of the material, and thus improving the cycle life of the secondary battery.
[0105] In some embodiments, before the graphitization step, the shaping material is also pre-carbonized. The pre-carbonization step is beneficial to reduce the volatile components in the binder, thereby reducing the impurity content in the first negative electrode active material, and improving the gram capacity and compaction density of the first negative electrode active material, so that the secondary battery can improve the cycle performance while taking into account the energy density.
[0106] In some embodiments, the pre-carbonization is performed under a protective atmosphere, illustratively, the protective atmosphere may be nitrogen or argon. In an optional embodiment, the pre-carbonization is performed under a nitrogen atmosphere.
[0107] In some embodiments, the pre-carbonization temperature is 1000°C-1500°C. Exemplarily, the pre-carbonization temperature can be 1000°C, 1100°C, 1200°C, 1300°C, 1400°C, 1500°C, or a value between the ranges consisting of any two of them. By making the pre-carbonization temperature within the above range, the volatile components contained in the raw materials can be fully removed, which is beneficial to reduce the number of impurities and defects in the artificial graphite, thereby increasing the gram capacity of the artificial graphite. In addition, the pre-carbonization treatment can increase the density of the raw materials and increase the amount of raw materials loaded in the furnace during the graphitization process. In an optional embodiment, the pre-carbonization temperature is 1100°C-1200°C.
[0108] In some embodiments, the pre-carbonization time is 1-4 hours. Exemplary pre-carbonization time may be 1 hour, 2 hours, 3 hours, 4 hours, or a range consisting of any two of these values.
[0109] The preparation method of the second negative electrode active material in the present application comprises the following steps:
[0110] Pretreatment step: crushing and shaping the calcined needle coke to obtain a shaped material; the calcined needle coke has a carbon content of more than 97%, a volatile component content of less than 2%, and a sulfur content of less than 0.5%;
[0111] Granulation step: mixing the shaping material with a binder to obtain a granulated material;
[0112] Graphitization step: subjecting the granulated material to a second graphitization treatment at 3000° C.-3200° C. to obtain a second artificial graphite with La(110) of 130nm-175nm and Lc(002) of 30nm-42nm as a second negative electrode active material.
[0113] In the present application, calcined needle coke is used as raw material. The needle structure of calcined needle coke is stronger and the mosaic structure is less. Using calcined needle coke as raw material is beneficial to reduce the content of impurities in the second artificial graphite, thereby improving the graphitization degree of the second artificial graphite.
[0114] In the present application, the carbon content of the calcined needle coke is more than 97%, the volatile component content is less than 2%, and the sulfur content is less than 0.5%. Here, the so-called volatile component refers to hydrocarbons with lower molecular weight, such as light alkanes. The sulfur content and volatile components of the calcined needle coke are within the above range, and the purity of the raw material is good, which is conducive to the development of grains during graphitization, reduces the number of defects in the graphitization process, and increases the graphitization degree of the second artificial graphite and the La (110) value of the artificial graphite. By making the La (110) of the second artificial graphite 130nm-175nm, and the Lc (002) 30nm-42nm, the development of graphite grains in the material is better, which is conducive to the embedding of active ions, thereby increasing the gram capacity and compaction density of the negative electrode film layer, and increasing the energy density of the secondary battery.
[0115] In the present application, the temperature of the graphitization treatment is 3000°C-3200°C. The graphitization temperature within the above range is conducive to the growth and development of graphite grains, improves the graphitization degree of the second artificial graphite, and then improves the gram capacity of the second artificial graphite, and improves the energy density of the secondary battery. Exemplarily, the graphitization temperature can be 3000°C, 3050°C, 3100°C, 3150°C, 3200°C, or a value between the ranges consisting of any two of them.
[0116] In the present application, high-purity raw materials are used and the graphitization temperature is controlled at 3000°C-3200°C, which is beneficial to the development of the 110 crystal planes of the graphite grains along the a-axis during the graphitization process, thereby increasing the La (110) value of the artificial graphite. In addition, it is also beneficial to reduce the number of defects in the graphitization process, thereby facilitating the improvement of the energy density of the secondary battery.
[0117] Those skilled in the art can adjust the graphitization time as needed. For example, an Acheson graphitization furnace can be used for graphitization treatment, and when the temperature is above 2800° C., the graphitization time can be 2-8 days.
[0118] In some embodiments, the softening point of the adhesive is 180°C-270°C. The softening point of the adhesive refers to the temperature at which the adhesive changes from a solid state to a softened state with a certain fluidity. In the present application, the softening point can be tested using instruments and methods known in the art, for example, it can be measured with reference to GB / T4507-2014. When the softening point of the adhesive is within the above range, the molecular weight of the polycyclic aromatic hydrocarbons in the adhesive is large and the content is high, which is conducive to improving the adhesion of the adhesive and reducing the amount of the adhesive in the granulation step, thereby increasing the gram capacity and compacted density of the second artificial graphite. Exemplarily, the softening point of the adhesive can be 180°C, 200°C, 220°C, 240°C, 260°C, 270°C or a value between the ranges consisting of any two of them.
[0119] In some embodiments, the coking value of the adhesive is 50%-70%. The coking value of the adhesive refers to the percentage of the mass of the coke residue formed after the adhesive is heated, burned or otherwise treated under specific experimental conditions to the mass of the original sample. In the present application, the coking value can be tested using methods known in the art. Exemplarily, it can be determined with reference to GB / T 8727-2008. The coking value of the adhesive within the above range is conducive to increasing the gram capacity and compaction density of the second negative electrode active material, thereby improving the energy density of the secondary battery.
[0120] In some embodiments, the mass ratio of the shaping material to the adhesive is 100:(6-12). The ratio of shaping material to adhesive within the above range is conducive to reducing the amount of residual carbon caused by the adhesive, increasing the gram capacity and compaction density of the second negative electrode active material, and thus improving the energy density of the secondary battery.
[0121] In some embodiments, before the graphitization step, the granulated material is also pre-carbonized. The pre-carbonization step is beneficial to reduce the volatile components in the binder, thereby reducing the impurity content in the second negative electrode active material, increasing the gram capacity and compaction density of the second negative electrode active material, and improving the energy density of the secondary battery.
[0122] In some embodiments, the pre-carbonization is performed under a protective atmosphere, illustratively, the protective atmosphere may be nitrogen or argon. In an optional embodiment, the pre-carbonization is performed under a nitrogen atmosphere.
[0123] In some embodiments, the pre-carbonization temperature is 1000-1500°C. Exemplarily, the pre-carbonization temperature can be 1000°C, 1100°C, 1200°C, 1300°C, 1400°C, 1500°C, or a value between the ranges consisting of any two of them. By making the pre-carbonization temperature within the above range, the volatile components contained in the raw material can be fully removed, which is beneficial to reduce the number of impurities and defects in the second artificial graphite, thereby increasing the gram capacity of the second artificial graphite. In addition, the pre-carbonization treatment can increase the density of the raw material and increase the amount of raw material loaded in the graphitization process. In an optional embodiment, the pre-carbonization temperature is 1000°C-1100°C.
[0124] In some embodiments, the pre-carbonization time is 1-4 hours. Exemplary pre-carbonization time may be 1 hour, 2 hours, 3 hours, 4 hours, or a range consisting of any two of these values.
[0125] In some embodiments, the volume distribution particle size Dv50 of the intermediate is 15 μm-18 μm. The particle size of the intermediate within the above range is conducive to increasing the particle size of the second artificial graphite, thereby increasing the gram capacity of the second artificial graphite and improving the energy density of the secondary battery.
[0126] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0127] In some embodiments, the first negative electrode active material and the optional conductive agent, the optional binder and other optional additives can be dispersed in a solvent (e.g., deionized water) to form a first slurry. The second negative electrode active material and the optional conductive agent, the optional binder and other optional additives can be dispersed in a solvent (e.g., deionized water) to form a second slurry. The above-mentioned binder can be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS). The conductive agent can be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers. In some embodiments, the negative electrode film layer may also optionally include other additives, such as a thickener (e.g., sodium carboxymethyl cellulose (CMC-Na)).
[0128] Positive electrode
[0129] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector, wherein the positive electrode film layer includes the positive electrode active material of the first aspect of the present application.
[0130] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.
[0131] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0132] In some embodiments, when the battery cell is a lithium-ion battery, the positive electrode active material may adopt a positive electrode active material for lithium-ion batteries that is well known in the art. As an example, the positive electrode active material may include at least one of the following materials: a lithium-containing phosphate with an olivine structure, a lithium transition metal oxide, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3Mn 1 / 3 O2 (also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523 )、LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.1 Al 0.05 O2) and its modified compounds, etc. Examples of lithium-containing phosphates with an olivine structure may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.
[0133] The battery will be accompanied by Li deintercalation and consumption during the charge and discharge process, and the molar content of Li is different when the battery is discharged to different states. In the list of positive electrode active materials in this application, the molar content of Li is the initial state of the material, that is, the state before feeding. The positive electrode active material is used in the battery system, and the molar content of Li will change after charge and discharge cycles.
[0134] In the list of positive electrode active materials in this application, the molar content of O is only a theoretical value. The release of oxygen from the lattice will cause the molar content of oxygen to change, and the actual molar content of O will fluctuate.
[0135] In some embodiments, the positive electrode film layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0136] In some embodiments, the positive electrode film layer may further include a conductive agent, which may include, for example, at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0137] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0138] Electrolytes
[0139] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.
[0140] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.
[0141] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.
[0142] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.
[0143] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.
[0144] Isolation film
[0145] In some embodiments, the battery cell further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.
[0146] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0147] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.
[0148] In some embodiments, the battery cell may include an outer packaging, which may be used to encapsulate the electrode assembly and the electrolyte.
[0149] In some embodiments, the outer packaging of the battery cell may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the battery cell may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0150] The present application has no particular limitation on the shape of the battery cell, which may be cylindrical, square or any other shape. Figure 2 The battery cell 5 is a square structure as an example.
[0151] In some embodiments, reference Figure 3 , the outer packaging may include a shell 51 and a top cover assembly 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the top cover assembly 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the battery cell 5 can be one or more, and those skilled in the art can select according to specific actual needs.
[0152] In some embodiments, battery cells may be assembled into a battery module. The number of battery cells contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.
[0153] Figure 4 4 is an example of a battery module. Figure 4 In the battery module 4, the plurality of battery cells 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of battery cells 5 may be fixed by fasteners.
[0154] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of battery cells 5 are received in the receiving space.
[0155] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.
[0156] Figure 5 and Figure 6 1 is a battery pack 1 as an example. Figure 5 and Figure 6 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.
[0157] In addition, the present application also provides an electric device, which includes a secondary battery provided in the present application. The secondary battery can be used as a power source for the electric device, or as an energy storage unit for the electric device. The electric device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.
[0158] As the electrical device, a battery cell, a battery module or a battery pack can be selected according to its usage requirements.
[0159] Figure 7The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the high power and high energy density requirements of the power consumption device for the secondary battery, a battery pack or a battery module can be used.
[0160] As another example, the device may be a mobile phone, a tablet computer, a notebook computer, etc. The device is usually required to be light and thin, and a battery cell may be used as a power source.
[0161] Example
[0162] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0163] Preparation of the first negative electrode active material
[0164] Materials 1-1
[0165] Step 1: crushing and shaping petroleum coke (sulfur content of 0.6%, volatile content of 12%) to obtain a shaped material of primary particles with a volume distribution particle size Dv50 of 12.8 μm;
[0166] Step 2: pre-carbonizing the above-mentioned shaped material at 1150° C. in a roller kiln to obtain an intermediate;
[0167] Step 3: The above intermediate is graphitized at 2450° C. to obtain material 1-1 as the first negative electrode active material.
[0168] Materials 1-2 to 1-5 and materials 1-1' to 1-2'
[0169] The preparation methods of materials 1-2 to 1-5 and materials 1-1' to 1-2' are similar to that of material 1-1, except that the type of raw materials, the particle size Dv50 of the shaping material and the graphitization temperature in the preparation method are adjusted according to the parameters shown in Table 1.
[0170] For the above materials, the test was carried out according to the following method, and the results are shown in Table 1
[0171] Test of graphitization degree of materials:
[0172] Refer to the test method in JIS K 0131-1996, use Bruker D8 Discover X-ray diffractometer for testing, using copper target as anode target, CuKα ray as radiation source, ray wavelength The scanning 2θ angle range is 20°-80°, and the scanning rate is 4° / min, and the average interlayer spacing d002 of the C(002) crystal plane in the material crystal structure is obtained, and then the graphitization degree is calculated according to the formula g=(0.344-d002) / (0.344-0.3354)×100%. In the above formula, d002 is the average interlayer spacing of the C(002) crystal plane in the material crystal structure expressed in nanometers (nm).
[0173] Test of OI value of powder material :
[0174] Refer to the test method in JIS K 0131-1996, use Bruker D8 Discover X-ray diffractometer for testing, use copper target as anode target, use CuKα ray as radiation source, and the ray wavelength is The scanning 2θ angle range is 20°-80°, and the scanning rate is 4° / min to obtain the X-ray diffraction pattern of the powder sample. According to the X-ray diffraction pattern, I 004 and I 110 , where I 004 is the integrated area of the diffraction peak of the 004 crystal plane of crystalline carbon in the powder sample, I 110 It is the integrated area of the diffraction peak of the 110 crystal plane of crystalline carbon in the powder sample. According to OI value = I 004 / I 110 The powder OI value of the sample is calculated.
[0175] Test of Gram Capacity of Materials :
[0176] The prepared sample powder was mixed evenly with the conductive agent carbon black (Super P), the binder polyvinylidene fluoride (PVDF) and the solvent N-methylpyrrolidone (NMP) in a mass ratio of 91.6:1.8:6.6 to prepare a slurry; the prepared slurry was coated on the surface of the negative electrode current collector copper foil, dried in an oven and set aside; ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) were mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then LiPF6 was dissolved in the organic solvent to prepare an electrolyte with a concentration of 1 mol / L. A metal lithium sheet was used as the counter electrode, and a 12μm polyethylene (PE) film was used as the isolation membrane, and the prepared electrolyte was assembled into a CR2430 button cell in an argon-protected glove box.
[0177] After the obtained button battery was allowed to stand for 12 hours, at 25°C, the prepared button battery was first discharged at a constant current of 0.15 mA to 0.005 V, allowed to stand for 10 minutes, and then discharged at a constant current of 50 μA to 0.005 V, allowed to stand for 10 minutes, and then discharged at a constant current of 10 μA to 0.005 V, and the first-cycle discharge capacity of the button battery was recorded; thereafter, the button battery was charged at a constant current of 0.3 mA to 2.0 V, and the first-cycle charging capacity of the button battery was recorded. The ratio of the first-cycle charging capacity to the mass of the material is the gram capacity of the material.
[0178] Volume distribution particle size test of materials :
[0179] Dv50 test: referring to GB / T 19077-2016 particle size distribution laser diffraction method, the test was carried out using Mastersizer 3000 laser particle size analyzer from Malvern Instruments Ltd., UK.
[0180] Testing of the compacted density of powder materials :
[0181] Take a certain amount of powder and put it in a special compaction mold, then put the mold on the compaction density instrument, set the pressure to 50000N, and the thickness of the powder under the pressure (thickness after pressure relief) can be read on the equipment. The compaction density can be calculated through ρ=m / v.
[0182] I D / I G Value Test
[0183] Horiba LabRAM HR800 Raman spectrometer was used for testing. The test conditions were: excitation wavelength of 532nm, grating of 600 lines, objective lens of 50 times, integration time of 10s, accumulation times of 3 times, surface scanning, obtaining the D peak and G peak intensities of 100 points, and calculating the I peaks of 100 points. D / I G , remove the largest and smallest 30 I D / I G The average value of the remaining 40 points is the I D / I G .
[0184] Table 1:
[0185]
[0186] Preparation of the Second Negative Electrode Active Material
[0187] Materials 2-1
[0188] Step 1: The calcined needle coke raw material (carbon content of 98.5%, volatile content of 1.0%, sulfur content of 0.5%) is crushed and shaped by mechanical grinding to obtain a shaped material with a Dv50 of 11 μm;
[0189] Step 2: Use granulation asphalt with a softening point of 200° C. as the first adhesive to granulate the above-mentioned shaping material together through a granulation kettle to obtain granulated material, wherein the mass ratio of the shaping material to the first adhesive is 100:8.
[0190] Step 3: The granulated material is pre-carbonized at 1150° C. for 2 hours under a nitrogen atmosphere to obtain an intermediate.
[0191] Step 4: The intermediate is graphitized at a high temperature of 3020°C, and the graphitized particles are sieved and demagnetized to obtain a first carbon material with La (110) of 131.7 nm and Lc (002) of 32.5 nm as the first negative electrode active material 1-1.
[0192] Materials 2-2 to 2-4 and materials 2-1' to 2-2'
[0193] The preparation method of materials 2-2 to 1-4 and materials 2-1' to 2-2' is similar to that of material 2-1, except that the type of raw materials and the graphitization temperature are adjusted so that the La(110), Lc(002), La / Lc, powder OI value, gram capacity, powder compaction density and Dv50 of materials 2-2 to 2-4 and materials 2-1' to 2-2' are the values shown in Table 2.
[0194] For the above materials, parameters such as the powder OI value, gram capacity, powder compaction density and Dv50 of the materials were tested with reference to the method for preparing the above first negative electrode active material, and the results are shown in Table 2.
[0195] In addition, the above materials were tested according to the following method, and the results are shown in Table 2.
[0196] Tests of La(110), Lc(002), and La / Lc of materials:
[0197] Refer to the test method in JIS K 0131-1996, use Bruker D8 Discover X-ray diffractometer for testing, use copper target as anode target, use CuKα ray as radiation source, and the ray wavelength is The scanning 2θ angle range is 20°-80°, and the scanning rate is 4° / min. The peak intensity and half-maximum full width (FWHM) of the diffraction peak corresponding to the (110) crystal plane of the material and the peak intensity and half-maximum full width (FWHM) of the diffraction peak corresponding to the (002) crystal plane are obtained, and then La and Lc are calculated according to the following formula:
[0198] La calculation formula:
[0199] Where: K is the shape factor, which is 1.84; λ is the wavelength (nm); β110 is the half-peak width of the 110 crystal plane corresponding to ~43° in the X-ray diffraction pattern; θ110 is the diffraction angle corresponding to the 110 crystal plane in the X-ray diffraction pattern
[0200] Lc calculation formula:
[0201] Where: K is the shape factor, which is 0.89; λ is the wavelength (nm); β002 is the half-peak width of the 002 crystal plane corresponding to ~26° in the X-ray diffraction spectrum; θ002 is the diffraction angle corresponding to the 002 crystal plane in the X-ray diffraction spectrum
[0202] The proportion of the platform's lithium-ion capacity to the total capacity is X
[0203] The sample powder was mixed evenly with the conductive agent carbon black (Super P), the binder polyvinylidene fluoride (PvDF) and the solvent N-methylpyrrolidone (NMP) in a mass ratio of 91.6:1.8:6.6 to prepare a slurry; the prepared slurry was coated on the surface of the negative electrode current collector copper foil, dried in an oven and set aside; ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) were mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then LiPF6 was dissolved in the above organic solvent to prepare an electrolyte with a concentration of 1 mol / L; and then the metal lithium sheet was used as the counter electrode. , polyethylene (PE) film as an isolation membrane, and the above electrolyte were assembled into a CR2430 button cell in an argon-protected glove box; the button cell was left to stand for 12 hours, and then at 25°C, it was first discharged to 0.005V at a constant current of 0.15mA, left to stand for 10 minutes, and then discharged to 0.005V at a constant current of 50μA again, left to stand for 10 minutes, and then discharged to 0.005V at a constant current of 10μA again; then it was charged to 2.0V at a constant current of 0.3mA, and the relationship between the charge and discharge capacity and voltage of the material was obtained, that is, the charge and discharge curve. The lithium insertion capacity of the lithium insertion platform appearing in the range of 0.005V-0.070V in the discharge curve is recorded as C1, and the total lithium insertion capacity in the range of 0.005V-2.0V is recorded as C2, then the lithium insertion capacity of the platform accounts for X=C1 / C2*100%.
[0204] Table 2:
[0205]
[0206] Example 1
[0207] (1) Preparation of the first negative electrode active material slurry
[0208] The first negative electrode active material, conductive agent Super P, thickener sodium carboxymethyl cellulose, and binder styrene-butadiene rubber were fully stirred and mixed in a proper amount of solvent deionized water at a weight ratio of 96.6:0.80:1.0:1.6 to form a first negative electrode active material slurry.
[0209] (2) Preparation of Second Negative Electrode Active Material Slurry
[0210] The second negative electrode active material, conductive agent Super P, thickener sodium carboxymethyl cellulose, and binder styrene-butadiene rubber were fully stirred and mixed in a proper amount of solvent deionized water at a weight ratio of 96.6:0.80:1.0:1.6 to form a second negative electrode active material slurry.
[0211] (3) Preparation of negative electrode sheet
[0212] The first negative electrode active material slurry and the second negative electrode active material slurry are extruded simultaneously through a double-chamber coating device, wherein the mass ratio of the first negative electrode active material slurry to the second negative electrode active material slurry is 1:1. The second negative electrode active material slurry is coated on the negative electrode current collector copper foil, that is, the second negative electrode active material slurry is coated on the lower area, and the first negative electrode active material slurry is coated on the second negative electrode active material slurry, that is, the first negative electrode active material slurry is coated on the upper area. After drying and cold pressing, a negative electrode sheet is obtained.
[0213] (4) Preparation of positive electrode sheet
[0214] Lithium iron phosphate: conductive carbon black: PVDF = 96.5:1.7:1.8 was mixed in a mass ratio, and then solvent N-methylpyrrolidone was added and stirred evenly to obtain a positive electrode slurry. The positive electrode slurry was coated on both surfaces of the positive electrode current collector aluminum foil, and after drying and cold pressing, a positive electrode sheet was obtained.
[0215] (5) Preparation of lithium-ion batteries
[0216] A polyethylene film is used as the separator, PVDF slurry is sprayed on both sides of the separator, and a 1μm ceramic coating is sprayed on one side, with the ceramic coating facing the cathode electrode.
[0217] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then LiPF6 is dissolved in the above organic solvent to prepare an electrolyte with a concentration of 1 mol / L.
[0218] The positive electrode sheet and negative electrode sheet prepared above are placed in order, so that the isolation film is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then the electrode assembly is obtained by winding; the electrode assembly is placed in an outer package, and after drying, the electrolyte is injected, and a secondary battery is obtained after vacuum packaging, standing, forming, shaping and other processes.
[0219] Example 2
[0220] The battery preparation method of Example 2 is similar to that of Example 1, except that, in the step of preparing the negative electrode sheet, the types of the first negative electrode active material and the second negative electrode active material are adjusted as shown in Table 3.
[0221] Comparative Example 1
[0222] The battery preparation method of Comparative Example 1 is similar to that of Example 1, except that, in the step of preparing the negative electrode sheet, the first negative electrode active material slurry is coated on the lower region, and the second negative electrode active material slurry is coated on the upper region.
[0223] Comparative Example 2
[0224] The battery preparation method of Comparative Example 2 is similar to that of Example 1, except that, in the preparation step of the negative electrode sheet, the first negative electrode active material 1-1 and the negative electrode active material 2-1 are evenly mixed to prepare a negative electrode slurry, and a single-layer negative electrode film layer is formed on the negative electrode current collector.
[0225] Comparative Example 3
[0226] The battery preparation method of Comparative Example 3 is similar to that of Example 1, except that, in the step of preparing the negative electrode sheet, only the first negative electrode active material 1-1 is used to form a single negative electrode film layer on the negative electrode current collector.
[0227] Comparative Examples 4-5
[0228] The battery preparation method of Comparative Examples 4-5 is similar to that of Example 1, except that, in the preparation step of the negative electrode sheet, the types of the first negative electrode active material and the second negative electrode active material are adjusted as shown in Table 3.
[0229] Performance Testing
[0230] (1) Gram capacity of negative electrode
[0231] Assemble a button cell with the negative electrode plate and the lithium plate, let the obtained button cell stand for 12 hours, then discharge it at 0.05C constant current to 0.005V at 25°C, let it stand for 10 minutes, discharge it at 50μA constant current to 0.005V, let it stand for 10 minutes, discharge it at 10μA constant current to 0.005V, the obtained capacity is the lithium-embedded gram capacity of the negative electrode plate; then charge it at 0.1C constant current to 2V, the obtained capacity is the lithium-de-embedded gram capacity of the negative electrode plate.
[0232] (2) Compacted density of negative electrode
[0233] The pole piece was cut into small discs with a diameter of 13 mm. The mass and thickness of the small discs were measured by a balance and a micrometer. The pole piece density was calculated according to the formula PD (density) = m (mass) / V (volume).
[0234] (3) Energy density
[0235] At 25°C, charge the secondary battery to 3.65V at 1 / 3C constant current, then charge to 0.05C at 3.65V, let stand for 5 minutes, then discharge to 2.5V at 1 / 3C constant current, and record the battery discharge energy at this time. The battery discharge energy divided by the battery weight is the battery weight energy density, in Wh / kg.
[0236] (4) Cycle performance test of secondary batteries
[0237] At 45°C, the secondary battery was charged at 1C constant current to an upper limit of 3.65V (corresponding to 100% SOC), then charged at constant voltage to a current of 0.05C. After standing for 5 minutes, the secondary battery was discharged at 1C constant current to 2.5V (corresponding to 0% SOC), and the discharge capacity at this time was recorded, which was the discharge capacity of the first cycle. The secondary battery was subjected to cyclic charge and discharge tests according to the above method, and the discharge capacity after each cycle was recorded.
[0238] Capacity retention rate of secondary battery after 1000 cycles at 45° C. (%)=discharge capacity after 1000 cycles / discharge capacity at the first cycle×100%.
[0239] The secondary batteries prepared in the above examples and comparative examples were subjected to performance tests, and the results are shown in Table 3.
[0240] Table 3
[0241]
[0242] According to the data in Table 3, it can be seen that compared with Comparative Examples 1 and 2, in the secondary battery prepared in Examples 1-2 of the present application, the negative electrode plate adopts a double-layer design, the first region adopts a first negative electrode active material with a low degree of graphitization and high isotropy, and the second region adopts a second negative electrode active material with a high energy density, thereby, the secondary battery can improve the cycle performance while taking into account the energy density. The secondary battery of Comparative Example 3 uses a negative electrode plate prepared from the first negative electrode active material, which has good cycle performance, but low energy density. In contrast, Examples 1-2 of the present application adopt a double-layer design, which can improve the cycle performance of the secondary battery while taking into account the improvement of energy density.
[0243] Example 3-12
[0244] The battery preparation methods of Examples 3-12 are similar to those of Example 1, except that the types and mass ratios of the first negative electrode active material and the second negative electrode active material are different.
[0245] The performance of the secondary battery prepared in the above embodiment was tested, and the results are shown in Table 4.
[0246] Table 4
[0247]
[0248]
[0249] It can be seen from the data in Table 4 that the secondary battery prepared in the examples of the present application can improve the cycle performance while taking into account the energy density.
[0250] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A secondary battery, comprising a negative electrode plate, characterized in that: The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer located on at least one surface of the negative electrode current collector, the negative electrode film layer has a first surface away from the negative electrode current collector and a second surface arranged opposite to the first surface, the thickness of the negative electrode film layer is recorded as H, the area within the thickness range from the first surface of the negative electrode film layer to 0.3H is recorded as the first area of the negative electrode film layer, and the area within the thickness range from the second surface of the negative electrode film layer to 0.3H is recorded as the second area of the negative electrode film layer, the first area includes a first negative electrode active material, and the second area includes a second negative electrode active material, The first negative electrode active material comprises primary particles of first artificial graphite, the powder OI value of the first negative electrode active material is 3-6, and the degree of graphitization is 91%-93.5%, The gram capacity of the second negative electrode active material is greater than the gram capacity of the first negative electrode active material.
2. The secondary battery according to claim 1, characterized in that: The powder OI value of the first negative electrode active material is 3-3.8, and / or the degree of graphitization is 91.0%-92.5%.
3. The secondary battery according to claim 1 or 2, characterized in that: The first negative electrode active material D / I G The value is 0.08-0.17; Among them, I D Indicates that the Raman spectrum of the material is at 1350±50cm -1 The D peak intensity at I G Indicates that the Raman spectrum of the material is 1580±50cm -1 The G peak intensity at I D / I G The values represent the ratio of the D peak intensity to the G peak intensity.
4. The secondary battery according to claim 3, characterized in that: The first negative electrode active material D / I G The value is 0.1-0.
15.
5. The secondary battery according to any one of claims 1 to 4, characterized in that: The gram capacity of the second negative electrode active material is greater than 359.0 mAh / g.
6. The secondary battery according to any one of claims 1 to 5, characterized in that: The gram capacity of the first negative electrode active material is 335 mAh / g-350 mAh / g.
7. The secondary battery according to claim 6, characterized in that: The gram capacity of the first negative electrode active material is 335 mAh / g-345 mAh / g; and / or The gram capacity of the second negative electrode active material is 360 mAh / g-366 mAh / g.
8. The secondary battery according to any one of claims 1 to 7, characterized in that: The powder compaction density of the first negative electrode active material at 50000N is less than the powder compaction density of the second negative electrode active material at 50000N.
9. The secondary battery according to any one of claims 1 to 8, characterized in that: The powder compaction density of the first negative electrode active material at 50000N is 1.65g / cc-1.83g / cc; and / or, The powder compaction density of the second negative electrode active material under a pressure of 50000N is 1.95g / cc-2.04g / cc.
10. The secondary battery according to claim 9, characterized in that: The powder compaction density of the first negative electrode active material at 50000N is 1.65g / cc-1.71g / cc; and / or, The powder compaction density of the second negative electrode active material under a pressure of 50000N is 1.96-2.02 g / cc.
11. The secondary battery according to any one of claims 1 to 10, characterized in that: The first negative electrode active material has a lower degree of graphitization than the second negative electrode active material.
12. The secondary battery according to any one of claims 1 to 11, characterized in that: The graphitization degree of the second negative electrode active material is 94.0%-96.0%.
13. The secondary battery according to claim 12, characterized in that: The graphitization degree of the second negative electrode active material is 94.2%-95.8%.
14. The secondary battery according to any one of claims 1 to 13, characterized in that: The volume distribution particle size Dv50 of the first negative electrode active material is 9.0 μm-13.5 μm; and / or, The volume distribution particle size Dv50 of the second negative electrode active material is 14.5 μm-18.0 μm.
15. The secondary battery according to claim 14, characterized in that: The volume distribution particle size Dv50 of the first negative electrode active material is 12.5-13.5 μm; and / or, The volume distribution particle size Dv50 of the second negative electrode active material is 15.0 μm-17.5 μm.
16. The secondary battery according to any one of claims 1 to 14, characterized in that: The specific surface area of the first negative electrode active material is less than or equal to the specific surface area of the second negative electrode active material.
17. The secondary battery according to any one of claims 1 to 16, characterized in that: The specific surface area of the first negative electrode active material is 0.8 m 2 / g-1.8m 2 / g; and / or, The specific surface area of the second negative electrode active material is 0.8 m 2 / g-2.1m 2 / g.
18. The secondary battery according to any one of claims 1 to 17, characterized in that: The secondary battery meets one or more of the following conditions: The gram capacity of the negative electrode plate is 348.0 mAh / g-355.0 mAh / g; The powder compaction density of the negative electrode film layer under a pressure of 50000N is 1.60g / cc-1.70g / cc; The surface density of the negative electrode film layer is 10.0 mg / cm 2 -20.0mg / cm 2 ; The thickness of the negative electrode film layer is 70 μm-250 μm.
19. The secondary battery according to any one of claims 1 to 18, characterized in that: In the negative electrode film layer, the mass ratio of the first negative electrode active material to the second negative electrode active material is 3:7-6:
4.
20. The secondary battery according to any one of claims 1 to 19, characterized in that: The second negative electrode active material includes a second artificial graphite, wherein La(110) of the second artificial graphite is 130nm-175nm, and Lc(002) is 30nm-42nm, La(110) indicates the size of the crystallites along the a-axis in the (110) crystal plane of the material, and Lc(002) indicates the size of the crystallites along the c-axis in the (002) crystal plane of the material.
21. The secondary battery according to claim 20, characterized in that: The La(110) of the second artificial graphite is 132nm-172nm, and the Lc(002) is 30nm-36nm.
22. The secondary battery according to claim 20 or 21, characterized in that: La(110) / Lc(002) is 3.5-5.
5.
23. The secondary battery according to any one of claims 1 to 22, characterized in that: The button cell prepared from the second artificial graphite was subjected to charge and discharge tests at a lithium desorption rate of 0.1C and a lithium insertion rate of 0.05C, respectively, to obtain a charge and discharge curve in the range of 0.005V-2.0V. In the discharge curve, there is a lithium insertion platform in the voltage range of 0.005V-0.070V, and the discharge capacity corresponding to the lithium insertion platform accounts for more than 43% of the total discharge capacity of the button cell.
24. The secondary battery according to claim 23, characterized in that: The proportion X of the discharge capacity corresponding to the lithium embedded platform to the total discharge capacity of the button cell is 43%-47%.
25. The secondary battery according to any one of claims 1 to 24, characterized in that: The second artificial graphite includes secondary particles.
26. The secondary battery according to any one of claims 1 to 25, characterized in that: The particle size distribution of the second negative electrode active material is (Dv90-Dv10) / Dv50 is 0.9-1.
25.
27. An electrical device, characterized in that: A secondary battery comprising the secondary battery according to any one of claims 1 to 26.
Citation Information
Patent Citations
Secondary battery, device, artificial graphite, and preparation method
CN113207313A
Composite artificial graphite and preparation method thereof, and secondary battery and electric device containing composite artificial graphite
CN116724002A
Negative pole piece, secondary battery, battery module, battery pack and electric device
CN116982170A
Secondary battery and electric device
CN117063306A
Secondary battery and electric device
CN117558918A
Cited By
Secondary battery and electric device
CN120432492A
Battery cell, battery device and electric device
CN121192270A
Secondary battery and electric device
WO2026045360A1